ARIMA- GARCH และ ARIMA- EGARCH Comparing the Accuracy of Forecasting Methods for the B/$ Exchange Rate between ARIMA- GARCH and ARIMA- EGARCH Models - Suebpongsakorn, Auttapol; Wisagarn, Supatra (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
This study aimed to select the best model for forecasting the Thai baht vs US Dollar between ARIMA - GARCH and ARIMA - EGARCH Models. The study was based on secondary data using the daily values of the Thai baht vs US dollar exchange rate from January 2, 2006 to September 30, 2014, the data covering a total of 2,282 observations. The result showed that the time series were stationary at 1st difference. Besides, the forecasting results of the Thai exchange rate revealed that the ARIMA (2,1,2) with EGARCH (1,1) has the lowest value of RMSE and MAPE followed by ARIMA (2,1,2) with GARCH (1,1). Thus, we can conclude that the ARIMA (2,1,2) with EGARCH (1,1) is the most accurate model for forecasting the Thai baht vs US dollar exchange rate.